2021
DOI: 10.23971/altarib.v9i2.3263
|View full text |Cite
|
Sign up to set email alerts
|

Teacher's Personality as a Motivation in Arabic Learning: A Systematic Review Based on Five Professional Teacher Personality Frameworks

Abstract: Studies on the factors that influence students' enthusiasm for learning Arabic are still focused on the strategies and media used. Therefore, this paper presents a systematic study of various educator personalities that can motivate students to learn Arabic. This research used a literature study approach. The articles were selected using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) approach and were analyzed using a framework of five professional teacher personalities. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…Furthermore, the involvement of teaching staff with proficiency in Arabic language is a key factor in the success of the learning program. Previous studies have shown that highquality teaching has a significant impact on student learning outcomes (Anggraini et al, 2021;Hamidah et al, 2022). The importance of regular program evaluation is also emphasized in this study.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, the involvement of teaching staff with proficiency in Arabic language is a key factor in the success of the learning program. Previous studies have shown that highquality teaching has a significant impact on student learning outcomes (Anggraini et al, 2021;Hamidah et al, 2022). The importance of regular program evaluation is also emphasized in this study.…”
Section: Discussionmentioning
confidence: 79%
“…Kompetensi pedagogik menyangkut tujuh hal yakni memahami karakter peserta didik, teori belajar, pengembangan kurikulum, pembelajaran yang mendidik, pengembangan potensi peserta didik, penilaian, dan evaluasi (Wulandari & Hendriani, 2021). Sedangkan kompetensi kepribadian menyangkut kestabilan, kedewasaan, kearifan, kewibawaan, dan kemuliaan (Anggraini et al, 2021). Kompetensi profesional menyangkut penguasaan materi, standar kompetensi hingga tujuan pembelajaran, pengembangan materi pembelajaran serta pemanfaatan teknologi informasi dan komunikasi (Fatchurrohman, 2019;Jamilah, 2020).…”
Section: Pendahuluanunclassified
“…Arabic is considered a key to knowledge because many sources of knowledge use this language. In Indonesia, Arabic is not only taught as a religious language but also as a language of knowledge (Anggraini et al, 2021;Mubarak et al, 2021). However, learning Arabic presents its own challenges due to its complexity, such as the different alphabet with 28 consonants, and the continuous changes in verb forms.…”
Section: Introductionmentioning
confidence: 99%